OVERVIEW OF HYDROPHYSICAL STUDIES IN THE WATERS OF THE DANUBE RIVER ESTATES - Nevierova S.I. (Геологія і корисні копалини Світового океану, 2022)
The purpose of the article is to systematize the hydrophysical observations carried out by various specialists in the waters of the Danube River region on the basis of the results of expeditionary studies carried out on the basis of long-term observations of the past and present centuries, the need to fill in the gaps in the understanding of the current state of the Danube sea mouth, due to a substantial increase in its anthropogenic load. The Danube Sea Floor is located on the Danube River. Data have been collected from many complex marine expeditionary studies on the Danube coastline of different institutions of different countries. A description of changes in the indicators of salinity, turbidity, run-off and sediment, oxygen, temperature, hydrogen index, upwelling, ecological state of the area of the estuary rise of the Danube region is provided. The practical significance of these results lies in the importance of establishing national inter-institutional cooperation for the efficient and rational use of natural resources and the introduction of environmental protection measures in the Danube and the Black Sea, introduction of world best practices for the sustainable development of territories, scientific management of water resources, establishment of a monitoring system to identify constructive solutions for the conservation and reproduction of aquatic bioresources in the Danube region and the adjacent territories of the Black Sea.